2005
DOI: 10.1111/j.1600-0722.2004.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical fit of all‐ceramic three‐unit fixed partial dentures, generated with three different CAD/CAM systems

Abstract: In this study, the hypothesis was tested that the marginal and internal fit of CAD/CAM fabricated all-ceramic three-unit fixed partial dentures (FPDs) can be as good as in metal-ceramic FPDs. Twenty-four all-ceramic FPDs were fabricated and randomly subdivided into three equally sized groups. Eight frameworks were fabricated using the Digident CAD/CAM system (DIGI), another eight frameworks using the Cerec Inlab system (INLA). Vita Inceram Zirkonia blanks were used for both groups. In a third group frameworks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
258
8
26

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(310 citation statements)
references
References 10 publications
18
258
8
26
Order By: Relevance
“…This finding is in agreement with other studies that investigated the adaptation of Y-TZP FPDs produced with LAVA and other current CAD-CAM systems. 3,5,17,20 An investigation also found significantly different mean gap values as a function of measurement location. 3 The study reported that the occlusal gap width of LAVA three-unit framework was six times larger than the marginal gap width.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This finding is in agreement with other studies that investigated the adaptation of Y-TZP FPDs produced with LAVA and other current CAD-CAM systems. 3,5,17,20 An investigation also found significantly different mean gap values as a function of measurement location. 3 The study reported that the occlusal gap width of LAVA three-unit framework was six times larger than the marginal gap width.…”
Section: Discussionmentioning
confidence: 96%
“…Although the sintering shrinkage of restorations obtained from partially sintered blocks can be compensated by milling enlarged restorations, it is not as yet clear whether this compensation is effective for the production of FPDs with long spans. 4,17 In addition, previous studies reported that the internal adaptation of CAD-CAM restorations is poorer, compared with marginal adaptation. 3,5,17 This finding represents a relevant clinical problem, insofar as wide internal gaps have been associated with decreased fracture strength and loss of retention of the restoration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, production steps 1 and 2 take place in the dental laboratory, while the third step takes place in the centre. 5,8 As a result, the configuration of the prosthe sis remains in the hands of the dental technician. The benefit of outsourcing CAM production is to be found in the small investment requirement, since only the digitalisation tool and soft ware have to be purchased, still having access to a high quality production pro cess.…”
Section: C) Centralised Productionmentioning
confidence: 99%
“…5). 8,28 c) Processing in hot isostatic pressing condition Some systems also process zirconium oxide in HIP (hot isostatic pressed) con dition with diamond tools and water cooling. The advantages and disadvan tages are as follows.…”
Section: B) White Stage Processingmentioning
confidence: 99%